Homeostasis Psikologi pada Anak Penderita Disgrafia akibat Tumor Otak - Annisa Dina Amalia; Rifa'ati Maulani Abdulloh; Ambar Sulianti (UIN Sunan Kalijaga, 2016)
A study has conducted in a 7 years old childwith dysgraphia due to brain tumor who has a good ability psychological homeostasis. Psychological homeostasis is a process of maintaining stability and psychological adaptation to the environmental conditions that occur continuously. This study aims to determine the causes and factors that affect the homeostasis of psychological research on the subject. This study is a qualitative research with survey techniques, observation, and interviews on acase study. The case study was chosen because this approach makes researcher gain a complete understanding of the interrelation and integrated facts and dimensions of the particular case studied. The result of this study indicates family factor and education of parent play important role in the homeostatic capability psychological research on the subject.